Theoretical Foundations for Developing Receptive Skills in Second Language Acquisition (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Receptive skills, namely listening and reading comprehension, are fundamental for effective communication in a second language (L2). This paper explores the theoretical underpinnings of receptive skill development, encompassing cognitive processing models, linguistic frameworks, and socio-cultural perspectives. By synthesizing existing research, this article aims to provide a comprehensive overview of the factors that contribute to successful L2 receptive skill acquisition.